Shedding light on the next pandemic path, from outpatient to ICU, the effect of vitamin D deficiency in the SARS-CoV-2 pandemic - Celikmen, F.; Tunaligil, V.; Keles, E. C.; Celikmen, D. S. M.; Sarikaya, S. (Frontiers in Nutrition, 2024)
Background: Vitamin D insufficiency is named "the pandemic of our era" by some experts.World Health Organization warns against a "deadlier outbreak" than the COVID-19 pandemic. Critical evidence is hereby for future pandemic prevention, with special emphasis on Vitamin D. Methods: A cross-sectional study was conducted with 172 unvaccinated adult participants, who presented to the emergency department. Blood measurements, radiological findings, and demographic features were evaluated in the four categories of "healthy adults, COVID-19 outpatients, hospitalized inpatients on the wards, and in the ICU". Results:were statistically significant in association with age, gender, weight, Vitamin D, glucose, urea, creatinine, leucocyte, aspartate transaminase, hemoglobin, C-reactive protein, troponin, platelet/thrombocyte, ferritin, D-dimer, triglycerate, glycated haemoglobin, lactate dehydrogenase measurements, and chest Computed Tomography features (each p<0.050). Conclusions: This article presents novel evidence and highlights evidence to support the importance of Vitamin D for global public health. Patients with adequate levels of Vitamin D, glucose, urea, creatinine, leucocyte, aspartate transaminase, hemoglobin, C-reactive protein, troponin, platelet/thrombocyte, ferritin, D-dimer, triglycerate, glycated haemoglobin, lactate dehydrogenase are less likely to be admitted to ICU versus being outpatients. Factors include gender, age, weight, comorbidities, and Computed Tomography findings. The ultimate goal is to globally minimize preventable burdens of disease and death.